Efficiency Of Lidar Technologies in Constructing Digital Terrain Models During Large-Scale Topogeodetic Surveys - Yurii Vodopianov (The American Journal of Applied Sciences, 2025)
In this study a comprehensive analysis of the efficiency of implementing LiDAR technology (Light Detection and Ranging) in the formation of high-precision digital terrain models (DTMs) in the course of large-scale topogeodetic surveys is carried out. The aim of the research is to evaluate LiDAR accuracy indicators, economic feasibility and operational performance relative to classical photogrammetry, taking into account the use of unmanned aerial vehicles (UAVs). The methodological basis of the research includes a review of publications, synthesis of data from these works and statistical data analysis. The results obtained indicate that LiDAR provides an advantage in digitizing terrain under dense vegetation cover. An algorithm for selecting the optimal method is proposed, based on multi-criteria analysis which includes vegetation density, accuracy requirements and project budget constraints. The key findings of the study emphasize the superiority of LiDAR in complex natural-landscape conditions and the economic viability of photogrammetry in areas with open terrain, which justifies the feasibility of a hybrid approach to optimize costs and improve the quality of the output DTMs. The study will be useful for surveying engineers, GIS specialists, managers of construction and infrastructure projects, as well as researchers in the field of Earth remote sensing.